Pengaruh Media Pembelajaran Ular Tangga Raksasa Terhadap Minat Belajar Siswa Pada Mata Pelajaran PKn Kelas 4 SD Muhammadiyah 08 Medan - Rizki Syahfitri; Sahkholid Nasution; Riris Nurkholidah Rambe (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The research that has been carried out entitled "The Influence of Using Giant Ladder Snakes Learning Media as Innovative Media on Student Learning Interests in Civics Class 4 Subjects at SD Muhammadiyah 08 Medan" aims: (1) To determine student learning interest in Civics subjects without using snake learning media giant ladder in grade 4 SD Muhammadiyah 08 Medan; (2) To find out students' learning interest in Civics subject using giant ladder snake learning media in grade 4 SD Muhammadiyah 08 Medan; (3) To describe the significant effect of the use of giant ladder snake learning media on students' learning interest in Civics subjects in grade 4 SD Muhammadiyah 08 Medan. This study uses a quantitative approach, with a quasi-experimental design research type. The design uses a non-equivalent control group design. The population in this study were all 4th graders and the samples were selected based on a purposive sampling technique, namely class 4A as the experimental class and 4B as the control class. Data collection techniques in this study were distributing questionnaires and documentation. Data analysis technique used is descriptive statistical analysis, normality test, homogeneity test, hypothesis testing using independent sample T-test, coefficient of determination and simple regression analysis. The results of the research that has been done can be concluded that: (1) Students' interest in Civics without using the giant ladder snake learning media in grade 4 SD Muhammadiyah 08 Medan is very low. This can be seen in the results of the pre-test questionnaire scores in the experimental class of 993 with 17 students as respondents. (2) Students' interest in Pkn subjects using giant ladder snake learning media in grade 4 SD Muhammadiyah 08 Medan is very high. This can be seen in the results of the post-test scores of the interest in learning questionnaire in the experimental class of 1138 with 17 students as respondents. Meanwhile, the results of the pre-test questionnaire were only 993. From this comparison, it can be concluded that students are very interested in learning Civics by using these learning media. (3) There is a significant effect of using giant ladder snake learning media on students' learning interest in Civics subjects in grade 4 SD Muhammadiyah 08 Medan. This can be proven by looking at the results of the independent sample t-test, the average value of the experimental class is greater than that of the control class with a score of 66.94 > 60.70 with a significance value (2-tailed) 0.000 <0.05. In addition, the results of the determination test with the help of the SPSS 26 application obtained an R Square value of 0.881, which means that the influence of the giant snakes and ladders learning media on students' learning interest was 88.1%. While the simple linear regression hypothesis test results obtained a significance value of 0.000 <0.05. This it can be concluded that there is a significant influence between the giant ladder snake learning media on students' learning interest in Civics class 4 SD Muhammadiyah 08 Medan. In other words, Ha is accepted and Ho is rejected.